A Review on Different Benefit for Annona muricata Fruits as Antioxidant (Iraqi Journal of Medical Sciences, 2020)
More than 200 chemical compounds have been identified and isolated from Annona muricata fruits and the most important such as alkaloids, phenols and acetogenins. Number of investigations have interested for this plant including antidiabetic, anticancer, anticonvulsant, anti-arthritic, anti-parasitic, antimalarial, analgesic hypotensive, anti-inflammatory and enhancing of immune system in addition to its content of high form antioxidants, which are vital to human health. Because these it the World Health Organization recommends the minimum consumption of fruit 120 kg/person/year.Keywords: Annona muricata, oxidation, health, cytotoxic activity, phytochemicals and traditional medicineCitation: Jassim HS. A review on different benefit for Annona muricata fruits as antioxidant. Iraqi JMS. 2020; 18(1): 1-3. doi: 10.22578/IJMS.18.1.1
Keywords: Annona muricata; oxidation; health; cytotoxic activity; phytochemicals and traditional medicine